The Scholems : A Story of the German-Jewish Bourgeoisie from Emancipation to Destruction - Geller, Jay Howard (Book collections on Project MUSE., 2019)
"A collective biography of the family of the Jewish scholar Gershom Scholem and a social history of the Jewish middle class in Germany from the era of emancipation through the Holocaust"--